Laparoscopic splenectomy for splenomegaly using a homemade retrieval BAG - Su, Chia-Hung (Termedia Publishing House, 2013)
INTRODUCTION: Operating on an enlarged spleen via the laparoscopic approach presents several challenges. A homemade bag may facilitate retrieval of the enlarged spleen assisted by a laparoscope and save medical expense. AIM: To assess the feasibility and safety of laparoscopic splenectomy for moderate or massive splenomegaly using our technique and a homemade retrieval bag. MATERIAL AND METHODS: Fifty patients underwent laparoscopic splenectomy for moderate or massive splenomegaly which was defined as the major axis exceeding 17 cm by abdominal computed tomography. A homemade retrieval bag made from a commercial sterile infusion container which costs about US$ 1–2 per piece was used for spleen retrieval. Two transabdominal sutures for suspension of the retrieval bag were made to aid specimen removal in this technique. RESULTS: There were 31 males and 19 females with mean age of 56 ±11 years. Laparoscopic splenectomy was successfully completed in 49 of these 50 patients. Overall, mean operative time was 149 ±31 min (range: 100–252 min). Median estimated blood loss was 189 ±155 ml (range: 50–920 ml). There were 12 minor complications but no mortality. Time to discharge after surgery ranged from 3 to 9 (mean: 4.7 ±1.7 days). The average splenic weight was 729 ±74 g (range: 632–930 g). CONCLUSIONS: Our preliminary results indicate that laparoscopic splenectomy is feasible and safe for moderate or massive splenomegaly and may be a well-tolerated alternative to open splenectomy. Not only is the cost of our homemade retrieval bag low, but also it is easy to make and ready to use.